Parallel intramolecular DNA triple helix with G and T bases in the third strand stabilized by Zn(2+) ions - Khomyakova, E. B. (Oxford University Press, 2000)
We present evidence of formation of an intramolecular parallel triple helix with T•A.T and G•G.C base triplets (where • represents the hydrogen bonding interaction between the third strand and the duplex while . represents the Watson–Crick interactions which stabilize the duplex). The third GT strand, containing seven GpT/TpG steps, targets the polypurine sequence 5′-AGG-AGG-GAG-GAG-3′. The triple helix is obtained by the folding back twice of a 36mer, formed by three dodecamers tethered by hydroxyalkyl linkers (-L-). Due to the design of the oligonucleotide, the third strand orientation is parallel with respect to the polypurine strand. Triple helical formation has been studied in concentration conditions in which native gel electrophoresis experiments showed the absence of intermolecular structures. Circular dichroism (CD) and UV spectroscopy have been used to evidence the triplex structure. A CD spectrum characteristic of triple helical formation as well as biphasic UV and CD melting curves have been obtained in high ionic strength NaCl solutions in the presence of Zn(2+) ions. Specific interactions with Zn(2+) ions in low water activity conditions are necessary to stabilize the parallel triplex.